Configurations, deformations, mutations. Criteria of morphological analysis in adaptive reuse - Elena Guidetti; Alessandro Massarente (Agathón)
The reuse of existing buildings is a topic of strategic interest in a perspective of sustainability and efficient use of resources. Since many buildings tend to survive over time the functions for which they were designed, it is necessary to analyze reuse interventions through a diachronic process. Among the multiple factors that contribute to the project of a reuse intervention, a key aspect is constituted by the underlying morphology of its pre-existence. Therefore, starting from the hypothesis that a building whose original function has mutated can no longer be characterized through it, but rather through the permanence of its form, we intend to demonstrate that a project of adaptive reuse of a pre-existing building implies a morphological potential through which it is possible to determine diversified cognitive approaches and transformation scenarios.